The Confucian Concept of Learning and the Aesthetics of Human Experience: An Eco-Ontological Interpretation - Meyer, David (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2024)
This paper examines the Confucian concept of learning, or xue (學) , from the perspective of ecological humanism. Through a comparative interpretation, this paper attempts to disclose the significance of Confucian xue conceived as a practice of aesthetic appreciation and creativity, emphasizing in particular its function within an eco-centric worldview. The author reviews the relevant concepts of ecological humanism as expressed in the ideas of John Dewey and Thomas Alexander, then applies these as a theoretical framework for interpreting xue and its related concepts and practices as they appear in the Confucian text the Lunyu (論語). It is argued that xue is a process of developing and expressing virtuosity and artistry in the “arts of life,” and that its practice was understood as a direct participation in the creative development of nature. The significance of such a concept of learning for contemporary educational philosophy is discussed in conclusion.